DNA Ligase C1 Mediates the LigD-Independent Nonhomologous End-Joining Pathway of Mycobacterium smegmatis - Bhattarai, Hitesh (American Society for Microbiology, 2014)
Nonhomologous end joining (NHEJ) is a recently described bacterial DNA double-strand break (DSB) repair pathway that has been best characterized for mycobacteria. NHEJ can religate transformed linear plasmids, repair ionizing radiation (IR)-induced DSBs in nonreplicating cells, and seal I-SceI-induced chromosomal DSBs. The core components of the mycobacterial NHEJ machinery are the DNA end binding protein Ku and the polyfunctional DNA ligase LigD. LigD has three autonomous enzymatic modules: ATP-dependent DNA ligase (LIG), DNA/RNA polymerase (POL), and 3′ phosphoesterase (PE). Although genetic ablation of ku or ligD abolishes NHEJ and sensitizes nonreplicating cells to ionizing radiation, selective ablation of the ligase activity of LigD in vivo only mildly impairs NHEJ of linearized plasmids, indicating that an additional DNA ligase can support NHEJ. Additionally, the in vivo role of the POL and PE domains in NHEJ is unclear. Here we define a LigD ligase-independent NHEJ pathway in Mycobacterium smegmatis that requires the ATP-dependent DNA ligase LigC1 and the POL domain of LigD. Mycobacterium tuberculosis LigC can also support this backup NHEJ pathway. We also demonstrate that, although dispensable for efficient plasmid NHEJ, the activities of the POL and PE domains are required for repair of IR-induced DSBs in nonreplicating cells. These findings define the genetic requirements for a LigD-independent NHEJ pathway in mycobacteria and demonstrate that all enzymatic functions of the LigD protein participate in NHEJ in vivo.